User Needs for Enhanced Engagement with Cultural Heritage Collections - Lawless, Seamus; Sweetnam, Mark; O Siochru, Micheal (My University, 2012)
This paper presents research carried out in order to elicit user needs for the design and development of a digital library and research platform intended to enhance user engagement with cultural heritage collections. It outlines a range of user constituencies for this digital library. The paper outlines a taxonomy of intended users for this system and describes in detail the characteristics and requirements of these users for the facilitation and enhancement of their engagement with and use of textual and visual cultural artefacts.
The 16th International Conference on Theory and Practice of Digital Libraries, TPDL 2012
PUBLISHED
Paphos, Cyprus
Keywords: Cultural Heritage; User Engagement; Digital Engagement; Digital Humanities; Digital Libraries